Synergistic Effects of Stem Cell Integration on Cochlear Implant Performance in Sensorineural Hearing Loss: A Systematic Review and Meta-Analysis of Neural Preservation and Speech Perception - Dinera Anjani; Theresa Puspanadi; Ajeng Shanaz Santya Putri; Amelia Nisa (HM Publisher, 2026)
Background: Cochlear implantation represents the paramount intervention for severe-to-profound sensorineural hearing loss. However, device efficacy is fundamentally constrained by retrograde degeneration of spiral ganglion neurons and post-insertional intracochlear fibrosis. This study aimed to quantitatively evaluate the synergistic efficacy of integrating stem cell therapies with cochlear implants to preserve neural architecture and enhance auditory functional outcomes. Methods: A systematic review and meta-analysis were executed following PRISMA guidelines. Comprehensive searches of electronic databases utilized specific Medical Subject Headings targeting biohybrid electrodes, mesenchymal stem cells, and spiral ganglion survival. Inclusion criteria strictly selected controlled in vivo preclinical models and human clinical trials evaluating concurrent stem cell application with implantation. Risk of bias was assessed utilizing SYRCLE and ROBINS-I tools. Random-effects models synthesized Standardized Mean Differences for neural preservation, with subgroup analyses evaluating delivery modalities. Results: Eight pivotal studies met stringent inclusion criteria. Meta-analysis demonstrated a highly significant preservation of spiral ganglion density in stem cell-integrated cohorts compared to implant-alone controls (Pooled Standardized Mean Difference = 2.45; 95% Confidence Interval: 1.54–3.36; p < 0.001). Subgroup analysis revealed that electrode coating yielded superior neuroprotection compared to bolus injections. Electrophysiological data demonstrated significantly lowered Electrically Evoked Auditory Brainstem Response thresholds. Clinical cohorts exhibited stable impedances and rapid improvements in speech perception. Conclusion: Stem cell-integrated cochlear implants orchestrate a potent bio-electronic synergy, modulating neuroinflammation and mitigating neural degeneration primarily through paracrine neurotrophic signaling. This bio-electronic integration represents a transformative paradigm in auditory rehabilitation, maximizing the fidelity of neural stimulation and optimizing clinical outcomes.